Historical Dictionary of the Seventh-Day Adventists - Land, Gary (Rowman & Littlefield Publishers, 2014)
Seventh-day Adventism was born as a radical millenarian sect in nineteenth-century America. It has since spread across the world, achieving far more success in Latin America, Africa, and Asia than in its native land. In what seems a paradox, Adventist expectation of Christ’s imminent return has led the denomination to develop extensive educational, publishing, and health systems. Increasingly established within a variety of societies, Adventism over time has modified its views on many issues and accommodated itself to the “delay” of the Second Advent. In the process, it has become a multicultural religion that nonetheless reflects the dominant influence of its American origins. This second edition of Historical Dictionary of the Seventh-Day Adventists covers its history through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 600 cross-referenced entries on key people, cinema, politics and government, sports, and critics of Ellen White. This book is an excellent access point for students, researchers, and anyone wanting to know more about Seventh-day Adventism.